Oil spill contamination probability in the southeastern Levantine basin. Issue 1 (15th February 2015) - Goldman, Ron; Biton, Eli; Brokovich, Eran; Kark, Salit; Levin, Noam
Graphical abstract: Highlights: We have simulated virtual oil spills in Israel's exclusive economic zone. Realistic ocean and weather conditions were used. Spills were released near ship routes, mooring buoys, gas wells and pipes. Seasonal oil spill probability maps were created per infrastructure type. High probability areas were identified and related to ocean and weather patterns. Abstract: Recent gas discoveries in the eastern Mediterranean Sea led to multiple operations with substantial economic interest, and with them there is a risk of oil spills and their potential environmental impacts. To examine the potential spatial distribution of this threat, we created seasonal maps of the probability of oil spill pollution reaching an area in the Israeli coastal and exclusive economic zones, given knowledge of its initial sources. We performed simulations of virtual oil spills using realistic atmospheric and oceanic conditions. The resulting maps show dominance of the alongshore northerly current, which causes the high probability areas to be stretched parallel to the coast, increasing contamination probability downstream of source points. The seasonal westerly wind forcing determines how wide the high probability areas are, and may also restrict these to a small coastal region near source points. Seasonal variability in probability distribution, oil state, and pollution time is also discussed.